Factor Influencing the Application of Social Customer Relationship Management in Women-Headed Small and Medium Enterprises - Sathana, V. (University of Jaffna, 2024)
Purpose: A growing number of small and medium enterprises (SMEs) are headed by women, contributing to the economic empowerment of women and the overall advancement of gender equality. The study aims to discover the factors that influence the application of social customer relationship management (SCRM) in women-headed SMEs. Design/Methodology/Approach: This research applied quantitative research methodology. The researcher developed factors after reviewing the literature and previous studies. The study population is women-headed SMEs in the Northern Province. The SME sector is selected as the sample unit. A convenient sampling method is used to collect the data, and factor analysis is used to identify the factors using SPSS. Findings: The findings revealed six factors, namely, organizational environment, technological competence, leadership support, trust in SCRM, environmental characteristics, and firm innovativeness that influence the application of SCRM in women-headed SMEs. Among these factors, the organizational environment is a highly loaded factor with a high percentage of explained variance of 22%, the most important factor for the SCRM application in SMEs; technological competence and innovativeness are other important factors for SME development. Research limitation: This research scoped only the women-headed SMEs; future research should be conducted with a comparative study on SMEs with both genders. Implication: This research revealed that the application of SCRM empowers women SMEs to overcome cultural and vulnerability barriers. These social customers are technology-empowered, digitally enriched, intellectually and globally connected people. The policy developers should focus on the digital-based infrastructure in Sri Lanka.
Keywords: Social Customer Relationship Management; Women headed SMEs; Organizational environment; Technological competence and Innovativeness